A Big Data Integration Platform for Ideological and Political Education for Smart Campuses. (16th May 2022) - Xu, Dazhi; Gao, Yan; Tu, Tianyi; Xiao, Xiaoyong
Abstract : The advent of large data and the era of large data has brought significant impact and changes to human production and life. Through the acquisition, analysis, processing, prediction, and dissemination of big data in scientific research, large data has emerged as the source of advanced technological to generate global quantitative data. It not only reveals the gaps and deficiencies of traditional approaches to ideological and mechanical studies methods in obtaining ideological behavior but also information about academic subjects providing support for optimizing and innovative technology and ideological transformation and then conducting intellectual and practical research in colleges and universities. In the age of large digital data, the ideology and politics of education are facing modern domestic and foreign situations, as well as new characteristics and new needs for ideology and politics study. This makes ideology and politics research methods even more important, which is seen as an opportunity for continuous creation and innovation and also adapts to the requirements of the times and reality. Smart campus refers to an intelligent integrated environment for campus work, study, and life based on the Internet of Things. This integrated environment takes various application service systems as the carrier and fully integrates teaching, scientific research, management, and campus life. From the large-scale data era, the educational theory of whether colleges and universities' ideological and political research is rich or not supports more scientific theories to carry out psychological and mechanical research. It is evident that in the age of large data, the ideological and political research in colleges and institutes is not only a theoretical issue but also an important practical issue. Therefore, conducting ideological and political research in colleges and institutes in the age of large data has profound theoretical significance and great practical significance.